PENGARUH PENGETAHUAN DAN SIKAP TERHADAP PERILAKU PENGGUNAAN ANTIBIOTIK TANPA RESEP DOKTER - Rahmayanti Fitriah; Eka Karlina; Depy Oktapian Akbar; Fitri Handayani (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2023)
Antibiotics are drugs that are often prescribed, sold, and used throughout the world so that people still think that by using antibiotics all diseases can be cured. Many antibiotics are available without a prescription and cause someone to use antibiotics unwisely. The high use of antibiotics that are not appropriate in society causes antibiotic resistance. The purpose of this study was to determine the effect of knowledge and attitudes on the behavior of using antibiotics without a doctor's prescription in Ilung Pasar Lama Village, Batang Alai Utara District, Hulu Sungai Tengah Regency, South Kalimantan, Indonesia. This research is descriptive-analytic with a cross-sectional survey research design, sampling with a probability sampling technique. Data collection was carried out on 93 respondents using a questionnaire that had been tested for validity and reliability. The data analysis used was univariate and bivariate analysis with the chi-square test. The results showed that respondents had less knowledge of 55.9%, respondents who had less attitude of 63.4% and respondents who had less behavior of 38.7%. The results of the chi-square statistical test showed that there was no effect between knowledge on the behavior of using antibiotics without a doctor's prescription with a value of 0.118 (Sig. > 0.05) but there was an effect of attitudes towards the behavior of using antibiotics without a doctor's prescription with a value of 0.000 (Sig. <0, 05).